The Determinants of Stunting Among Children Under Five In Central Java Based On Indonesian Nutritional Status Survey 2022 - Suyatno; Lilis Wijayanti; Hasna Izdihar Latifah (Universitas Airlangga, 2026)
Stunting remains a major public health problem in Indonesia, particularly in densely populated provinces with a high rates of stunting cases, such as Central Java. The research aimed to investigate determinants of stunting among children under five in Central Java, utilizing the Indonesian Nutritional Status Survey (SSGI) 2022. The analyses included 65,323 children under five, applying a multistage cluster sampling design with complex-sample logistic regression. The strongest predictors of stunting were older child age (AOR=3.27; 95% CI: 2.36–4.53) and low birth weight (AOR=2.39; 95% CI: 2.02–2.84). Stunting occurred more frequently among children whose mothers had less education and from high parity, as well as those living in household with food insecurity. A consistent social gradient was observed, with children from the poorest households being more than twice as vulnerable to stunting as those from the wealthiest households (AOR=2.24; 95% CI: 1.87–2.68). Health care services gaps, including incomplete immunization, lack of Mid-Upper Arm Circumference (MUAC) monitoring, and absence of deworming tablets, significantly increased stunting risks, as did a history of pneumonia. Rural dwelling of children increased the odds for stunting when compared to residing in urban areas (AOR=1.20; 95% CI: 1.09–1.32). These findings underscore the combined influence of biological, maternal, socioeconomic, health service-related, and urban-rural disparities underlying stunting in Central Java. To accelerate stunting reduction, it is important to prioritize the implementation of multisectoral actions for strengthening maternal education, and early childhood optimum nutrition, food security, and reducing rural-urban disparities in access to quality primary health care.